Contraction velocity influence the magnitude and etiology of neuromuscular fatigue during repeated maximal contractions. Issue 5 (30th December 2014) - Morel, B.; Clémençon, M.; Rota, S.; Millet, G. Y.; Bishop, D. J.; Brosseau, O.; Rouffet, D. M.; Hautier, C. A.
Abstract : This study aimed to compare the magnitude and etiology of neuromuscular fatigue during maximal repeated contractions performed in two contraction modes (concentric vs isometric) and at two contraction velocities (30/s vs 240°/s). Eleven lower limb‐trained males performed 20 sets of maximal contractions at three different angular velocities: 0°/s (KE0), 30/s (KE30), and 240°/s (KE240). Cumulated work, number of contraction, duty cycle, and contraction time were controlled. Torque, superimposed and resting twitches, as well as gas exchange, were analyzed. Increasing contraction velocity was associated with greater maximal voluntary torque loss (KE0: −9.8 ± 3.9%; KE30: −16.4 ± 8.5%; KE240: −32.6 ± 6.3%; P < 0.05). Interestingly, the torque decrease was similar for a given cumulated work. Compared with KE0, KE240 generated a greater evoked torque loss (Db100 : −24.3 ± 5.3% vs −5.9 ± 6.9%; P < 0.001), a higher O2 consumption (23.7 ± 6.4 mL/min/kg vs 15.7 ± 3.8 mL/min/kg; P < 0.001), but a lower voluntary activation (VA) loss (−4.3 ± 1.6% vs −11.2 ± 4.9%; P < 0.001). The neuromuscular perturbations were intermediate for KE30 (Db100 : −10.0 ± 6.8%; VA: −7.2 ± 2.8%). Although the amount of mechanical work cumulated strongly determined the magnitude of torque decrease, the contraction velocity and mode influenced the origin of the neuromuscular fatigue. The metabolic stress and peripheral fatigue increased but reduction of VA is attenuated when the contraction velocity increased from 0°/s to 240°/s.